2011
DOI: 10.1007/s13142-011-0028-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Web-based intervention on women’s breast health behaviors

Abstract: Helping women make choices to reduce cancer risk and to improve breast health behaviors is important, but the best ways to reach more people with intervention assistance is not known. To test the efficacy of a Web-based intervention designed to help women make better breast health choices, we adapted our previously tested, successful breast health intervention package to be delivered on the Internet, and then we tested it in a randomized trial. We recruited women from the general public to be randomized to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…In the cancer field, use of online information by cancer survivors is well documented (22)(23)(24)(25)(26), and the Internet is being used as a resource for cancer-related information in the general population (27). These findings are complemented by evidence that online behavior change materials can achieve comparable effects to print-based or telephone modalities (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…In the cancer field, use of online information by cancer survivors is well documented (22)(23)(24)(25)(26), and the Internet is being used as a resource for cancer-related information in the general population (27). These findings are complemented by evidence that online behavior change materials can achieve comparable effects to print-based or telephone modalities (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Of these five studies, two studies Bowen et al 2011) reported an increase in screening uptake, and three studies Bowen et al 2011;Helmes et al 2006) reported better psychological outcomes such as cancer worry and quality of life.…”
Section: Type Of Risk Presentedmentioning
confidence: 99%
“…Though, the amount of detail that each study provided their participants with did all vary, therefore studies and their intervention material varied in the complexity. A total of thirteen studies (Allen et al, 2010;Bodurtha et al, 2009;Bowen & Powers, 2010;Bowen et al, 2011;Glenn et al, 2011;Harari et al, 2008;Helmes, Culver, & Bowen, 2006;Lipkus & Klein, 2006;Rawl et al, 2012;Schroy et al, 2011;Schroy et al, 2012;Steckelberg, Hulfenhaus, Haastert, & Muhlhauser, 2011;Yuksel, Majumdar, Biggs, & Tsuyuki, 2010;Yuksel, Tsuyuki, & Majumdar, 2012) provided participants with some form of educational material regarding a particular disease or condition or screening test. In two studies (Allen et al, 2010;Schroy et al, 2011;Schroy et al, 2012) the main focus was to aid decision making and a decision aid tool was used, where educational information was provided alongside a decision aid tool to assist in the decision making process about attending for screening.…”
mentioning
confidence: 99%
See 2 more Smart Citations